Pemberlakuan Golden Visa Mempermudah Investor Asing Menanamkan Modal Pada Perusahaan Lokal - Aldy Christian Tarigan; Angel Caroline; Muhammad Fauzan; Hadista Alkhalifi; Hervina H; Muhammad Syaiful Anwar (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The application of the Golden Visa is now being designed by the Directorate General of Immigration in launching investment facilitation by foreign investors, the declaration of the Golden Visa is to facilitate residence permits for foreign investors. The Stay Permit Scheme through Investmen and Citizenship by Investment, or often referred to as 'Golden Visa' and 'Golden Passport' schemes, is a policy imposed by a country through a mechanism for providing several facilities including facilities residence permit or citizenship to Foreign Citizens (WNA) through investment or paying a certain fee. Several countries use various terms in naming Golden Visa. Indonesia may use other terms, for example Visa or Limited Stay Permit. Golden Visa holders will enjoy exclusive benefits that are not received by visa holders in general, including easier and faster procedures and requirements for visa applications and immigration matters, mobility with multiple entries, longer stay periods, the right to own assets within the country, as well as being a fast track route for applying for citizenship. so that the facilitation for foreign investors in obtaining a residence permit is thought to be able to attract many foreign investors who are interested in investing both in the state, MSMEs, or also local companies.companies.